Lipofibromatosis-Like Neural Tumor: A Case Report and Review of the Literature. (November 2020) - Crumbach, Laura; Descotes, Françoise; Bringuier, Pierre-Paul; Poulalhon, Nicolas; Balme, Brigitte; Juliet, Tantot; Lopez, Jonathan; Harou, Olivier
Abstract : Abstract: Lipofibromatosis-like neural tumors (LPF-NT) are soft tissue tumors characterized by a lipofibromatosis-like pattern, CD34/PS100 positivity, and recurrent NTRK1 gene rearrangement. It occurs mainly in pediatric patients or young adults. We report here, the first case of LPF-NT in a middle-aged adult initially misdiagnosed as a myoepithelial tumor. LPF-NT may have a locally aggressive course but no recurrence was seen after complete surgeries, whereas metastatic diseases remain exceptional.